Cell-laden alginate hydrogels for the treatment of diabetes. (2nd August 2020) - Izeia, Lukin; Eufrasio-da-Silva, Tatiane; Dolatshahi-Pirouz, Alireza; Ostrovidov, Serge; Paolone, Giovanna; Peppas, Nicholas A.; De Vos, Paul; Emerich, Dwaine; Orive, Gorka
ABSTRACT: Introduction: Diabetes mellitus is an ever-increasing medical condition that currently suffers 1 of 11 adults who may have lifelong commitment with insulin injections. Cell-laden hydrogels releasing insulin may provide the ultimate means of correcting diabetes. Here, we provide insights of this cell-based approach including latest preclinical and clinical progress both from academia and industry. Area covered: The present article focuses on reviewing latest advances in cell-laden hydrogels both from the technological and biological perspective. The most relevant clinical results including clinical trials are also discussed. Expert opinion: Current progress in technological issues (stem cells, devices, biomaterials) have contributed cell encapsulation science to have a very relevant progress in the field of diabetes treatment.